Perseverance Island; Or, The Robinson Crusoe of the Nineteenth Century - Frazar, Douglas, 1836-1896; Merrill, Frank T., 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2014)
"Perseverance Island; Or, The Robinson Crusoe of the Nineteenth Century" by Douglas Frazar is a novel written in the late 19th century. This adventure story follows a character who, after a series of maritime disasters, finds himself shipwrecked on a deserted island in the South Pacific. Drawing on his ingenuity and skills, he attempts to survive and thrive in this unfamiliar environment, focusing on themes of resilience, resourcefulness, and the indomitable human spirit. The opening of the narrative introduces the protagonist and provides the backstory of his life as a sailor, detailing his aspirations for adventure that culminate in joining the ill-fated expedition aboard the schooner "Good Luck." After navigating treacherous seas and facing storms, the crew suffers devastating losses, leading to the shipwreck. The protagonist survives the chaos of the storm, finds himself washed ashore on an unknown island, and begins to contemplate his situation, setting the stage for his struggle for survival. Filled with emotional depth and survival challenges, the beginning wastes no time immersing the reader into the hardships faced by the protagonist, highlighting both his vulnerabilities and strengths. (This is an automatically generated summary.)
Release date is 2014-07-03
E-text prepared by sp1nd, Chris Whitehead, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Islands -- Juvenile fiction; Adventure stories; Fishing -- Juvenile fiction; Pirates -- Juvenile fiction; Family -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Hunting -- Juvenile fiction; Robinsonades; Gold -- Juvenile fiction; Utopias -- Juvenile fiction